2007
DOI: 10.1007/s11104-007-9499-7
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of Okinawa Island plants on the root-knot nematode Meloidogyne incognita (Kofoid and White) Chitwood

Abstract: In order to develop biological control methods that are effective against the root-knot nematode Meloidogyne incognita (Kofoid and White) chitwood, the activity of ethanolic and aqueous extracts of wild plant species distributed on Okinawa Island on the viability and mobility of second stage M. incognita juveniles (J2s) was evaluated. Eleven of the 29 extracts immobilized at least half of the J2 stage nematodes in an in vitro assay. Aqueous extracts of Bidens pilosa L. var. radiata Scherff, Hydrocotyle dichond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Other species of Asteraceae such as Stevia rebaudiana , Artemisia annua , Verbesina encelioides , Tithonia diversifolia , Bidens pilosa , Chrysanthemum cinerariaefolium , Chrysanthemum coronarium , C. segetum , Aster sedifolius , A. caucasicus , Achillea wilhelmsii , Ruta chalepensis , Gochnatia barrosii , Heterotheca inuloides , Eclipta prostrata , Vernonia amygdalina , among others are also a source of compounds known to have effective potency against PPNs (Caboni and Ntalli, 2004; Claudius-Cole et al, 2010 ; de Santos Júnior et al, 2010 ; Di Vito et al, 2010 ; Kepenekçi et al, 2016 ; Kim et al, 2016 ; Oka, 2012 ; Pérez et al, 2003 ; Taba et al, 2008 ). Stevia rebaudiana is mainly known for its sweet-tasting glycosides of steviol and is used as natural non-caloric sweetener ( Karaköse et al, 2015 ; Kinghorn and Soejarto, 1985 ).…”
Section: Composition Activity and Potency Of The Active Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species of Asteraceae such as Stevia rebaudiana , Artemisia annua , Verbesina encelioides , Tithonia diversifolia , Bidens pilosa , Chrysanthemum cinerariaefolium , Chrysanthemum coronarium , C. segetum , Aster sedifolius , A. caucasicus , Achillea wilhelmsii , Ruta chalepensis , Gochnatia barrosii , Heterotheca inuloides , Eclipta prostrata , Vernonia amygdalina , among others are also a source of compounds known to have effective potency against PPNs (Caboni and Ntalli, 2004; Claudius-Cole et al, 2010 ; de Santos Júnior et al, 2010 ; Di Vito et al, 2010 ; Kepenekçi et al, 2016 ; Kim et al, 2016 ; Oka, 2012 ; Pérez et al, 2003 ; Taba et al, 2008 ). Stevia rebaudiana is mainly known for its sweet-tasting glycosides of steviol and is used as natural non-caloric sweetener ( Karaköse et al, 2015 ; Kinghorn and Soejarto, 1985 ).…”
Section: Composition Activity and Potency Of The Active Constituentsmentioning
confidence: 99%
“…Furthermore, Di Vito et al (2010) demonstrated that by using leaf meal of A. caucasicus , reproduction of M. incognita was suppressed by 82.3 and 92.7% at an application rate of 0.5 and 1 g/100 cm 3 soil, respectively. Aqueous extracts of B. pilosa are also said to have significant immobilization, repellence, and lethality effects on M. incognita ( Taba et al, 2008 ).…”
Section: Composition Activity and Potency Of The Active Constituentsmentioning
confidence: 99%
“…Kök-ur nematodlarının mücadelesinde nematisitler yoğun olarak kullanılmalarına karşın yüksek toksik etkiye sahip olmaları, çevre ve insan sağlığına olan olumsuz etkileri nedeniyle kullanımları her geçen gün daha da sınırlandırılmaktadır. Son yıllarda nematisit özelliği olan çok sayıda aktif madde bu olumsuzluklar nedeniyle kullanımdan kaldırılmıştır (Taba et al 2008). Tüm bu nedenlerden dolayı nematodlar ile mücadele etmek için kimyasal mücadeleye alternatif, çevre dostu güvenli ve etkili kontrol yöntemlerine ihtiyaç duyulmaktadır (Noling and Becker 1994).…”
unclassified
“…These studies ( 35 , 37 ) also described a combined biological and chemical approach for controlling M. incognita using a simultaneous treatment with Monacrosporium ellipsosporum and a nematicide. In addition, Taba et al ( 36 ) investigated the nematicidal activity of extracts of a weed found primarily on Okinawa Island ( Bidens pilosa var. radiata ) on the J2s of M. incognita and found that it exhibited potent activity against M. incognita and other important nematodes ( 38 ).…”
mentioning
confidence: 99%